Reasons for outsourcing innovations and its effect on firm performance: Evidence from highly innovative firms from twenty countries - Zafar, Afnan (Technium Social Sciences Journal, 2020)
Innovative products have become crucial as firms vie for consumer attention in a saturated market. One important strategy is the use of external innovation providers. This study investigates reasons for outsourcing innovations (OI) and their relationship with firms’ performance. The results should assist firms in ascertaining how the reasons for OI affect firm performance. First, the conceptual framework of reasons for OI and related firm performance was synthesized from the open innovation literature. Then, highly innovative firms from twenty countries were surveyed and analysed using statistical tools. The results provided support for a conceptual framework with a positive relationship between five reasons for OI and firms’ overall performance. An implication for managers is that, if Contract Research Organisation (CRO) country’s environment is the only reason for entering into an OI contract, it might not be a good decision in terms of the respective firms’ overall performance.